Temporomandibular disorders in fibromyalgia: a critical view - Luana Maria Martins de Aquino; Maisa Soares Gui; Marcele Pimentel; Rubens Reimão; Célia Marisa Rizzatti-Barbosa (Brazilian Dental Science)
.